DEVICE FOR MEASURING BLOOD FLOW - HASEGAWA KINYA; NISHIMURA YUJI (1999)
PROBLEM TO BE SOLVED: To calculate automatically a blood flow in the artery from a distance between two pressure sensors by fixing the two pressure sensors onto the skin above the artery and providing a means of retaining the distance so that it may not change. SOLUTION: A pressure sensor 1 and a pressure sensor 2 are fixed to the lower arm of a subject for example, by an adhesive tape with a distance d determined in advance by a pressure sensor fixing plate 3. The pressure sensors 1, 2 detect fine vibrations of the skin above the artery due to a pulse wave, and the pulse wave signal is amplified with amplifiers 4, 5 and outputted. An MPU 7 computes a pulse wave propagation time T in a section in the artery for which the pressure sensors 1, 2 detect a pulse wave from a pulse wave signal detected by the pressure sensor 1 and a pulse wave signal detected by the pressure sensor 2. In addition, the MPU 7 computes a blood flow using the distance between the pressure sensor 1 and the pressure sensor 2 that is determined in advance by the pressure sensor fixing plate 3 as input parameters. The process from pulse wave detection to blood flow computation is executed automatically, making measurement easy to perform.